Increased TLR4 and TREM-1 expression on monocytes and neutrophils in preterm birth: further evidence of a proinflammatory state. (17th September 2019) - Yan, Huan; Li, Hong; Zhu, Linlin; Gao, Junjun; Li, Pengyun; Zhang, Zhan
Abstract: Objective: Increased inflammation is considered as a risk factor and a promoter of preterm birth (PTB). Monocytes and neutrophils are the main sources of cytokines in the early inflammatory phase. So far, very few studies have indicated CD14/TLR4 and TREM-1 on the monocytes and neutrophils as important targets in PTB. Materials and methods: TLR4 and TREM-1 on CD14 + maternal and cord blood monocytes and neutrophils were detected using flow cytometry in 48 normal term women, 48 PTB with chorioamnionitis (CCA) women, and 40 PTB without CCA women. In the fetal membranes, mRNA and protein levels of the CD14/TLR4-TREM-1 signaling pathway, CD14, TLR4, NF-κBp65, and TREM-1 were analyzed by qRT-PCR and western blot. ELISA was further used to detect TLR4 and TREM-1 levels in maternal and cord serums. Results: Compared with the normal term and PTB without CCA women, we found that (1) TLR4 and TREM-1 levels on CD14 + maternal and cord blood monocytes and neutrophils in the PTB with CCA group were elevated ( p  < .001); (2) the protein and mRNA expressions of CA14, TLR4, NF-κBp65, and TREM-1 of the PTB with CCA group were upregulated ( p  < .001); (3) Maternal and cord serum concentrations of TLR4 and TREM-1 in the PTB with CCA group were greater ( p  < .001). Conclusions: The high levels of TLR4 and TREM-1 surface expression were observed on CD14 + maternal and cord blood monocyte and neutrophils, confirming their proinflammatory profiles in PTB with CCA. TLR4 and TREM-1 on monocyte and neutrophils might have a role in infection-related PTB.